Mechanical properties of nanomaterials: A review - Wu, Qiong; Miao, Wei-shou; Zhang, Yi-du; Gao, Han-jun; Hui, David (Nanotechnology reviews (Berlin), 2020)
As an emerging material, nanomaterials have attracted extensive attention due to their small size, surface effect and quantum tunneling effect, as well as potential applications in traditional materials, medical devices, electronic devices, coatings and other industries. Herein, the influence of nanoparticle selection, production process, grain size, and grain boundary structures on the mechanical properties of nanomaterials is introduced. The current research progress and application range of nano-materials are presented. The unique properties of nano-materials make them superior over traditional materials. Therefore, nanomaterials will have a broader application prospect in the future. Research on nanomaterials is significant for the development and application of materials science.